Settle for more - Kelly, Megyn (New York, NY : HarperLuxe, an imprint of HarperCollins Publishers, 2016)
The autobiography of journalist Megyn Kelly, anchor of Fox News Channel's The Kelly File.
Tough questions -- No false praise -- Mean girls -- Silent night, holy night -- Who's getting hit first? -- Trial team Barbie -- Legally blond -- Self-pity is not attractive -- Calling and calling; nobody's home -- "Who's here?" "Me!" -- Lawyer, broadcaster, journalist -- So long, Little Miss Perfect -- Nights of fear -- Writing the wrong things -- All the days of my life -- The best line -- Now everyone's here -- Ready for prime time -- On "having it all" -- Election season -- The first debate -- Fallout -- Relentless -- The Trump Tower accords -- Paying it forward -- Settling for more today.
Includes bibliographical references (pages 481-490).
Keywords: Kelly, Megyn; Television news anchors -- United States -- Biography; Women television journalists -- United States -- Biography; Working mothers; Large type books